Moessbauer study of synthetic hematite aggregates. - Dang, Mei-Zhen. (University of Ottawa (Canada), 1992)
Synthetic hematite aggregates that result from a process that may have industrial and environmental relevance are studied by Mossbauer spectroscopy at room temperature and liquid nitrogen temperature. The Mossbauer results are compared to measurements involving chemical analysis, scanning electron microscopy, and X-ray diffraction on the same samples. Factors such as the crystalline quality of the hematite and the overall sample purity (wt%Fe$\sb2$O$\sb3)$ are followed as functions of the known synthesis conditions. Pure bulk hematite (high quality $\alpha$-Fe$\sb2$O$\sb3$) serves as a reference throughout. Mossbauer spectroscopy is useful in two ways in this problem: (i) it can detect and identify iron-bearing impurities (i.e. non-hematite Fe-compounds), and (ii) it gives much detailed microscopic information on the intra-sample hematite. We find that all of the sulphur seen by chemical analysis probably resides in an iron-bearing compound which, most often, is probably a quenstetite-like material: Fe$\sb2$(SO$\sb4)\sb3\cdot$nH$\sb2$O (n = 9-11). The synthesis conditions are understood to determine both the hematite yield (or sample purity: wt%Fe$\sb2$O$\sb3$) and the intra-hematite crystalline quality, in that these two factors are correlated. Our interpretation of the room temperature Mossbauer spectra resolves coexisting bulk-like and high-defect-density regions whose relative amounts and sample-dependent Mossbauer characteristics can be quantified accurately. On going to liquid nitrogen temperature, a Morin transition is seen to have occurred in all regions of the most bulk-like samples, to have occurred in some regions of intermediate samples, or not to have occurred at all in the samples with the highest defect-density hematites. This illustrates the intricate interplay between microstructural details and cooperative magnetism in hematite materials.
Keywords: Physics, Nuclear.